P.108: Organic Wrinkles as Optical Scattering Sources. Issue 1 (1st July 2013) - Moon, Jaehyun; Park, Seung Koo; Hwang, Joohyun; Cho, Nam Sung; Joo, Chul Woong; Huh, Jin Woo; Han, Jun‐Han; Shin, Jin‐Wook; Cho, Doo‐Hee; Lee, Jonghee; Ahn, Joon Tae; Lim, Jong Tae; et al.
Abstract: Various external actions can cause the formation of patterns. In this work, we describe the spontaneous formation of wrinkles in an organic material system. The appearance of the fairly complex wrinkle structures is ascribed to the stress release during UV curing process of the liquid prepolymer solution. The wrinkle structures introduced here are demonstrated to have a light extraction function.